Fatty Acids Composition of Microalga Botryococcus Sp. Cultured in Synthetic Medium - Abba, Zubainatu; Matias-Peralta, Hazel Monica; Mohammad Fuzi, Siti Fatimah Zahrah; Abakr, Yousif Abdalla; Mohammed, Isah Yakub; Nmaya, Muhammad Muhammad (Journal of Science and Technology, 2017)
In response to the crisis of fossil fuel depletion and global climate change, microalgae cultivation has received significant attention as an alternative to sustainable biodiesel production. In this study, the total fatty acids content was quantified from Botryococcus sp biomass grown in synthetic medium Bold Basal Medium (BBM) under laboratory conditions. The microalgal biomass was harvested through centrifugation in the late logarithmic growth phase and then it was freeze-dried at -40oC and 0.12 Mbar for 86400 s (24 hrs). The lipids were extracted following Soxhlet method, and the fatty acids were analyzed using GC–MS. From the results obtained, the fatty acid composition is; C16:0 (Palmitic acid) contributing 27.950%, followed by C18:3 (stearic acid 22.758%), followed by C 18:2 (linoleic acid17.046) and the lowest is C 15:1 (pentadecanoic acid) with 0.051%. Most of the fatty acids obtained are both saturated and unsaturated which are similar to the conventional biodiesel and diesel properties making this green microalga Botryococcus sp. a desirable feedstock for biodiesel production. Thus, this locally isolated Botryococcus sp. has a high potential to be used as a source of biodiesel in the future.